2022
DOI: 10.3920/jiff2021.0147
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-modified density effects in the black soldier fly: low larval density leads to large size, short development time and high fat content

Abstract: The effects of biotic and abiotic factors on insect life histories have been extensively studied. However, the impact of some crucial aspects, such as larval density (crowding) and the effects of environmental interactions, have often been overlooked. This study aims to determine the effects of larval density and temperature on life-history traits in the black soldier fly (BSF). Our results showed an increase in prepupal mass, pupal mass, prepupal-to-pupal mass loss, survival, prepupal fat content, adult mass,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 92 publications
(134 reference statements)
4
18
0
Order By: Relevance
“…Similar adverse effects of density on survival or growth have been reported in other insect species such as Drosophila melanogaster (Henry et al, 2020), Musca domestica (Kökdener and Kiper, 2020) or Tenebrio molitor (Deruytter and Coudron, 2022). Impaired larval DM content observed in the present work at high density suggests that limited access to feed caused BSFL to use their body energy resources by oxidising their fat reserve (Opare et al, 2022). However, FCR (dry to fresh) was improved by increasing density down to an asymptote, indicating that BSFL performance as a group outweighed each individual underperformance.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar adverse effects of density on survival or growth have been reported in other insect species such as Drosophila melanogaster (Henry et al, 2020), Musca domestica (Kökdener and Kiper, 2020) or Tenebrio molitor (Deruytter and Coudron, 2022). Impaired larval DM content observed in the present work at high density suggests that limited access to feed caused BSFL to use their body energy resources by oxidising their fat reserve (Opare et al, 2022). However, FCR (dry to fresh) was improved by increasing density down to an asymptote, indicating that BSFL performance as a group outweighed each individual underperformance.…”
Section: Discussionsupporting
confidence: 84%
“…Life history traits values obtained were consistent with data from the literature on chicken feed: Liu et al (2019) reported survival rates between 40 and 93% and Gold et al (2018) summarised that prepupal FM could range between 99 and 184 mg. Larval DM content were in the range of 17.9 to 38.8% reported by Bosch et al (2020). In the present study, high areal density caused stronger competition for feed resources, hence lower survival rate and individual FM and DM gain, as already observed (Brits, 2017;Jones et al, 2019;Opare et al, 2022). Dead BSFL could not be visually detected after seven days of feeding and were presumably consumed by other larvae or decomposed into the substrate.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies on larval density involving the larvae of economically important black soldier fly (Hermetia illucens, BSF) have shown that high larval densities have detrimental effects on central life-history traits such as prepupal mass, pupal mass, adult mass, and development time (Barragan-Fonseca et al, 2018;Jones and Tomberlin, 2019;Opare et al, 2022). However, BSF larvae are generally regarded as quite unsusceptible to diseases, and it has been suggested that they could inherently possess innate resistance to harmful microorganisms (Joosten et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The longer development time of the current larvae than the previous studies [ 13 , 14 , 15 ] could be attributed to the differences of experimental temperature and complexity of the food waste. Opare et al [ 35 ] reported that high temperatures of 27–30 °C resulted in shorter larval development time than a low temperature of 23 °C. The current experiment was conducted at the ambient temperature of 22–26 °C, which is lower than the reference temperature of 26–27 °C [ 13 , 14 , 15 ], thus contributing to the longer development time.…”
Section: Resultsmentioning
confidence: 99%